Worth dying for - Child, Lee (London Bantam Press, 2010)
There's deadly trouble in the corn country of Nebraska... and Jack Reacher walks right into it. First he falls foul of the Duncans, a local clan that has terrified an entire county into submission. But it's the unsolved case of a missing child, already decades-old, that Reacher can't let go.
111357
Keywords: Reacher, Jack -- (Fictitious character) -- Fiction; Retired military personnel -- Fiction; Suspense fiction; Nebraska -- Fiction; Thrillers (Fiction); Suspense fiction; Detective and mystery fiction